2009
DOI: 10.5194/angeo-27-2001-2009
|View full text |Cite
|
Sign up to set email alerts
|

Particle precipitation during NEIAL events: simultaneous ground based nighttime observations at Svalbard

Abstract: Abstract. In this paper we present Naturally Enhanced Ion Acoustic Lines (NEIALs) observed with the EISCAT Svalbard Radar (ESR) together with auroral emissions observed with the Meridian Scanning Photometer (MSP). This is the first report of NEIALs observed during nighttime at Svalbard. Previously, NEIALs have been associated with a strong red line intensity (>10 kR), which exceeds the green line intensities. The high intensity in the red line emission is a sign of abundant low energy electron precipitation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…F region NEIAL occurrence shows another small peak at 2100 MLT in Figure 3c, and then only E region NEIALs in Figure 4b show small peaks at 2100–2200 and 0000 MLT. Such NEIALs during nighttime hours at high latitudes were reported by Lunde et al [2009], and they were associated with the substorm expansion phase on the nightside.…”
Section: Resultssupporting
confidence: 56%
“…F region NEIAL occurrence shows another small peak at 2100 MLT in Figure 3c, and then only E region NEIALs in Figure 4b show small peaks at 2100–2200 and 0000 MLT. Such NEIALs during nighttime hours at high latitudes were reported by Lunde et al [2009], and they were associated with the substorm expansion phase on the nightside.…”
Section: Resultssupporting
confidence: 56%
“…Lunde et al . [] reported NEIALs associated with a substorm expansion phase on the nightside and their relation to auroral emissions with different wavelengths. They suggested that intensity enhancements in the 844.6 nm emission line could be a better candidate than the 630.0 nm emission as an optical signature for the NEIALs.…”
Section: Discussionmentioning
confidence: 99%